Urban Islamization and Increasing Preference for Integrated Islamic Schools in Jambi City: A Case Study Approach - Sai'in, Sai'in (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2024)
This study aims to examine the phenomenon of urban Islamization in Jambi City and how it influences community preferences towards integrated Islamic schools compared to public schools or other Islamic-based schools. Utilizing a case study approach, this research explores the role of Integrated Islamic Schools in integrating curricula and extracurricular activities that support Islamic character development. Data were collected through in-depth interviews, participatory observation, and document analysis from various related sources. The results show that changes in the urban community's mindset towards Islamic education are influenced by social and cultural dynamics, including the role of community and social networks in educational decision-making. Additionally, these findings reveal the implications of urban Islamization on educational preferences, challenges, and opportunities faced by Islamic schools in the context of urbanization. The limitations of this study include the generalizability of the findings beyond Jambi City. In conclusion, urban Islamization in Jambi has led the community to choose integrated Islamic schools as a superior educational option, reflecting a shift in values and expectations towards Islamic education in the modern era. This phenomenon also reflects the strengthening dynamics of urban Islamization in Jambi City